A1.14 Synovial macrophages promote TGF-β signalling but protect against influx of S100A8/S100A9-producing cells after intra-articular injections of oxidised low-density lipoproteins. (24th February 2016) - de Munter, W; Geven, EJW; Blom, AB; Walgreen, B; Helsen, MMA; Joosten, LAB; Roth, J; Vogl, T; van de Loo, FAJ; Koenders, MI; van den Berg, WB; van der Kraan, PM; et al.
Abstract : Background and objectives: LDL in inflamed synovium is oxidised and taken-up by macrophages, leading to an activated macrophage phenotype. In this study, we investigate whether injection of oxLDL directly into a murine knee joint induces joint pathology and elucidate the role of synovial macrophages in that process. Materials and Methods: Synovium was obtained from end-stage OA patients. Murine knee joints were injected five consecutive days with oxLDL, LDL, or vehicle (PBS). This procedure was repeated in mice depleted of synovial lining macrophages by intraarticular injection of clodronate liposomes seven days prior to the consecutive injections. Joint pathology was investigated by immunohistochemistry, flow cytometry (FCM) and synovial RNA expression and protein production. Results: Synovial macrophages and fibroblast of OA patients showed extensive accumulation apolipoprotein B, the main protein present in LDL and oxLDL. Multiple injections of oxLDL in murine knee joints significantly increased TGF-β activity in synovial wash-outs, but did not induce catabolic or inflammatory processes. In contrast, repeated injections of specifically oxLDL in macrophage-depleted knee joints led to increased synovial thickening. Furthermore, protein and RNA levels of CCL2 and CCL3 were significantly upregulated in macrophage-depleted joints after oxLDL injections and FCM-analyses revealed increased presence of monocytes and neutrophils in the synovium, which was confirmed by immunohistochemistry. Also protein levels of S100A8/A9 were significantly increased in synovial wash-outs of oxLDL-injected joints, as was expression of aggrecanase-induced neo-epitopes. Interestingly, no raise in active TGF-β was measured in macrophage-depleted joints. Conclusions: Synovial macrophages promote anabolic processes after oxLDL injections. In absence of synovial macrophages, however, oxLDL induces production of pro-inflammatory mediators and aggrecanase activity in combination with increased influx of monocytes and neutrophils.